Strategies for living with TBI-Simple not easy - Nancy Bauser (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Being interdependent with the environment must be the goal for the coping strategies that I use.  I choose who I want to be and how much I value who I am.  My feelings about myself are a combination of my self-concept and my level of self-esteem.  My self-concept is defined as, "Who I believe I am" and my self-esteem is rooted in how firm my belief is.